P75 and neural cell adhesion molecule 1 can identify pathologic Schwann cells in peripheral neuropathies. Issue 7 (2nd July 2019) - Kim, Young Hee; Kim, Young Hye; Shin, Yoon Kyung; Jo, Young Rae; Park, Da Kyeong; Song, Min‐Young; Yoon, Byeol‐A.; Nam, Soo Hyun; Kim, Jong Hyun; Choi, Byung‐Ok; Shin, Ha Young; Kim, Seung Woo; et al.
Abstract: Objective: Myelinated Schwann cells (SCs) in adult peripheral nerves dedifferentiate into immature cells in demyelinating neuropathies and Wallerian degeneration. This plastic SC change is actively involved in the myelin destruction and clearance as demyelinating SCs (DSCs). In inherited demyelinating neuropathy, pathologically differentiated and dysmyelinated SCs constitute the main nerve pathology. Methods: We investigated whether this SC plastic status in human neuropathic nerves could be determined by patient sera to develop disease‐relevant serum biomarkers. Based on proteomics analysis of the secreted exosomes from immature SCs, we traced p75 neurotrophin receptor (p75) and neural cell adhesion molecule 1 (NCAM) in the sera of patients with peripheral neuropathy. Results: Enzyme‐linked immunosorbent assay (ELISA) revealed that p75 and NCAM were subtype‐specifically expressed in the sera of patients with peripheral neuropathy. In conjunction with these ELISA data, pathological analyses of animal models and human specimens suggested that the presence of DSCs in inflammatory neuropathy and of supernumerary nonmyelinating or dysmyelinating SCs in inherited neuropathy could potentially be distinguished by comparing the expression profiles of p75 and NCAM. Interpretation: This study indicates that the identification of disease‐specific pathological SC stages might be a valuable tool for differential diagnosis of peripheral neuropathies.